Pengembangan dan Pelatihan Pembukuan Sederhana Berbasis Kas Pada Kelompok Kurma â€œUkhuwah Datu Nusantaraâ€ Kecamatan Gangga - Khalid Abjadi; Thatok Asmony; Endar Pituringsih; Muhammad Alfi Satia Pratama; Fathiah Rahman (Universitas Mataram, 2026)
Training and mentoring activities on the preparation of simple cash-based financial reports and the development of innovations were carried out to support the